Strategi Guru Dalam Meningkatkan Prestasi Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam Di MA Ma’arif Bakung Udanawu Blitar - Nik Haryanti; Rochmat Rochmat (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2023)
The implementation of educational institutions between teachers and students has a very close relationship in improving student achievement. School as an educational institution that seeks to form a generation that is reliable, faithful and pious, has noble character and is skilled through general and religious education and the majority of its students receive religious education from their parents, so that their academic achievement is lacking, seen in the daily behavior of students who often take actions that are violates student rules and there are still those who are not orderly in participating in religious activities, so that teacher strategies in improving student learning achievement are needed to minimize bad acts or morals committed by students. The research approach is qualitative research, with a descriptive research type. Data collection techniques are participant observation, in-depth interviews and documentation. The analysis technique used is data reduction, data presentation and conclusion. The results of the research are 1) Reflective strategies applied by the teacher in learning to improve student achievement in PAI subjects at MA Ma'arif Bakung Udanawu Blitar which are carried out by: a) the teacher brings different experiences into learning, b) helps students understand the material based on their experience c) the quality of assignments given by the teacher, demands the involvement of thought processes, and requires evaluation, d) the teacher conditions students in a learning environment including facilitators of implementation agendas, space and time of implementation, with a supportive learning environment, achievement student learning will be able to improve properly. 2) the espositoric strategy applied by the teacher in learning to improve student achievement in PAI subjects at MA Ma'arif Bakung Udanawu Blitar, by: a) preparing all material readiness, b) Emphasizing material through lecture and question and answer methods. c) giving a good example or role model to students, 3) heuristic strategies used by teachers in learning to improve student achievement in PAI subjects at MA Ma'arif Bakung Udanawu Blitar by activating a) teaching materials. b) Its implementation is preceded by an appreciation in advance and giving direction on the intent of the material objectives.